Effects of maxillary expansion on the upper airways: Evidence from systematic reviews and meta‐analyses. (10th February 2019) - Bucci, Rosaria; Montanaro, Danilo; Rongo, Roberto; Valletta, Rosa; Michelotti, Ambra; D'Antò, Vincenzo
Summary: Background: Constricted maxilla is frequently associated with reduced nasal airway dimensions. Wheatear skeletal maxillary expansion (ME) is effective on the dimension of the upper airways is still a debated issue. Objectives: This overview aimed to report the evidence provided by systematic reviews (SRs) on the effect of ME on the upper airways and to assess the methodological quality of the included SRs. Methods: Six electronic databases have been explored up to November 2017. After title and abstract screening, SRs addressing the effects of fixed palatal expanders on the dimension and function of the nasal airways were included. The methodological quality of the included SRs was assessed using the updated version of A Measurement Tool to Assess Systematic Review (AMSTAR‐2). Results: Eight SRs were included. The methodological quality of most of the included SRs ranged between low and critically low. One SR was rated of high quality. A significant increase in nasal linear dimensions was reported both in the short and long term, but supported by low‐/critically low‐quality SRs. The significant increase in nasal cavity volume was the only outcome supported by a high‐quality SR Controversial results were found with regards to nasal function. Conclusion: Whenever a constricted maxilla is present general dentists, paediatricians and ENTs should be familiar with the potential improvement provided by ME. However, due to the low/critically low quality of SRs supporting these results, ME cannot be indicated only for upper airways enhancement, but should be supported by an orthodontic indication.